2020
DOI: 10.20473/jn.v14i3.17173
|View full text |Cite
|
Sign up to set email alerts
|

The Difference Between the Conventional Warm Compress and Tepid Sponge Technique Warm Compress in the Body Temperature Changes of Pediatric Patients with Typhoid Fever

Abstract: Introduction: The use of warm compresses and warm sponge techniques as a modality therapy for the management of fever in typhoid children has a good influence. The purpose of this research was to learn of the differences between conventional warm compress and the tepid sponge technique as related to the body temperature changes of pediatric patients with typhoid fever. A fever that does not get a good standard of treatment can cause dehydration, neurological damage and febrile seizures.Methods: The research de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
0
5
0
6
Order By: Relevance
“…In another randomized clinical trial, carried out in India, with two experimental groups, IG1 (warm sponging) and IG2 (hot sponging), it is observed that the use of hot water can reduce the discomfort provided by the intervention (26) . However, in a quasi-experimental study carried out with 20 children with typhoid fever, in which 10 used hot compresses and 10 used warm sponging, without medication, both groups had a significant reduction in body temperature in the first 15 minutes (p.<0.05), but only sponging showed results after 30 minutes (p<0.05), and at the end of the evaluation, after 60 minutes, both were not significant, with an increase in temperature and fever recurrence (20) . Thus, the use of hot water is also controversial.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In another randomized clinical trial, carried out in India, with two experimental groups, IG1 (warm sponging) and IG2 (hot sponging), it is observed that the use of hot water can reduce the discomfort provided by the intervention (26) . However, in a quasi-experimental study carried out with 20 children with typhoid fever, in which 10 used hot compresses and 10 used warm sponging, without medication, both groups had a significant reduction in body temperature in the first 15 minutes (p.<0.05), but only sponging showed results after 30 minutes (p<0.05), and at the end of the evaluation, after 60 minutes, both were not significant, with an increase in temperature and fever recurrence (20) . Thus, the use of hot water is also controversial.…”
Section: Discussionmentioning
confidence: 89%
“…The use of warm compresses provides heat loss through conduction and convection mechanisms, similar to the sponging intervention, with loss by conduction, convection, and evaporation (20,27) . While there is a lack of research in the national territory addressing the use of warm compresses, there is a high number of international publications on sponging (11,20,27) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pengabdi merespon dengan memberikan penjelasan tentang pertolongan pertama kejang demam serta cara melakukan kompres hangat. Beberapa penelitian menunjukkan bahwa metode kompres hangat dengan suhu yang mendekati suhu normal tubuh terbukti efektif dalam menurunkan hipertermia pada anak jika dibandingkan dengan tepid sponge (Karra, Anas, Hafid, & Rahim, 2019). Hal ini lah yang mendasari kegiatan workshop pemberian kompres hangat dalam upaya menurunkan demam sebagai penyebab kejang pada anak.…”
Section: Pendahuluanunclassified